(untitled) (Rainbow: Journal of Literature, Linguistics and Culture Studies, 2026)
This study examines the fragmentation of self and the profound psychological contradictions of Ernest Burkhart’s character in David Grann’s novel Killers of the Flower Moon (2017). Filling the gap in previous research that mostly focused on the issues of postcolonialism, systemic exploitation, and racial violence at a macro level, this study specifically dissects the intrapsychic mechanisms of individuals experiencing personality splitting. This study is a descriptive qualitative study using a psychoanalytic literary criticism approach and Cartesian dualism. Data were taken from the main novel text and collected through close reading techniques, then classified the data to interpret the character’s internal contradictions. The results of the study through the lens of Cartesian dualism show a distance between Ernest’s mind (Res Cogitans)—which harbors affection, empathy, and genuine emotional dependence on his wife, Mollie—and the actions of his physical body (Res Extensa) that mechanically facilitate the conspiracy of the Osage family massacre. Furthermore, Freudian psychoanalysis diagnoses that this mind-body fragmentation is caused by the failure of the Ego’s function in mediating the Id’s material greed drive and the Superego’s demands distorted by moral submission to William Hale’s authority. The Ego’s failure to compartmentalize these roles triggers a split in the ego, so that ethical consciousness loses its executive power and leads to total moral collapse. This research asserts that human emotions and morality will lose their ethical significance if the Ego is completely paralyzed in mediating the clash between internal desires and the pressures of external reality.